A new plant guanosine cyclase ZjGC found from jujube regulates growth and development via endogenous hormones - Zhao, Xin; Cao, Haonan; Liu, Yao; Mai, Junyan; Yang, Fangyuan; Liu, Zhiguo; Liu, Mengjun (Frontiers in Plant Science, 2025)
Cyclic guanosine monophosphate (cGMP) is an important second messenger involved in many physiological processes. Guanylate cyclase (GC), the key synthetase of cGMP, has been identified in many microorganisms and mammals, but very few in plants for their poor cGMP level. The biological functions of GC and endogenous cGMP in plant remains largely unknown. Here, we found a new plant GC, ZjGC, from jujube (Ziziphus jujuba Mill.) rich in cGMP via genome-wide identification, and its function catalyzing cGMP synthesis was confirmed by in vitro enzymatic property analysis, transient overexpression in jujube fruit in vivo, and generation of transgenic plants of Micro-Tom tomato. Overexpressing ZjGC in tomato showed that ZjGC has vital biological functions of promoting seed germination, restraining plant height growth, shortening juvenile period, accelerating fruit development, increasing seed number, and decreasing the size of fruit and seed by increasing endogenous cGMP content with significant increase of GA3 and moderate decrease of IAA and ABA. A feedback regulation mechanism of cGMP to hormones GA3 and ABA was firstly discovered in plant. Adding cGMP to jujube calli significantly increased GA3 content, promoted calli growth and differentiation. This research lays a solid foundation for further study and utilization of GC and cGMP as well as the research on phytohormone signaling in plants.